Study on Suspended Particles Velocity at Ogee Dam Spillway Using Discrete Particle Method (DPM) and Particle Image Velocimetry (PIV) - Zahari N.M.; Zawawi M.H.; Sidek L.M.; Abas M.A.; Ghazali F.N.; Hassan N.H. (Springer Science and Business Media Deutschland GmbH, 2023)
Cerenkov counters; Cost effectiveness; Flow visualization; Spillways; Velocimeters; Velocity; Velocity control; Velocity measurement; Cost effective; Dam construction; Dam spillway; Discrete particle methods; High quality; Ogee dam; Particle velocities; Scaled modeling; Shield number; Suspended particles; Dams